A novel mechanical metamaterial with dramatically different elastic parameters in tension and compression. (March 2023) - Wu, Hao; Zhong, Rongchang; Chen, Wei; Fu, Minghui
Abstract: The elastic parameters of most mechanical metamaterials are invariable under tension-compression transition. In this paper, a novel 2D mechanical metamaterial is proposed by combining a re-entrant negative Poisson's ratio structure and a rhombic positive Poisson's ratio structure based on nonlinear contact. The mechanical properties of the metamaterial are investigated by analytical method, experiment, and numerical simulation. The results show that the Poisson's ratio of the metamaterial is always negative under tension, while it varies from negative to positive as the stiffness ratio of rhombic structure to re-entrant structure increases under compression. By appropriately adjusting the stiffness ratio of rhombic structure to re-entrant structure, we can obtain a metamaterial with different signs of Poisson's ratio under tension and compression or an auxetic metamaterial. In addition, the ratio of compressive modulus to tensile modulus of this metamaterial could be tuned between 1 and 90, depending on the geometrical and constituent material parameters. The metamaterial has simple mechanisms and great designability. Due to its unique mechanical properties, the design shows great potential in the fields of mechanical sensors and elastic wave modulation. Graphical Abstract: ga1